THE EFFECT OF SELF-EFFICACY ON THE INDEPENDENCE AND ACTIVITY OF ELEMENTARY SCHOOL STUDENTS' LEARNING: SYSTEMATIC LITERATURE REVIEW - Cindy Putri Ranny Azhari; Sigit Wibowo (Jurnal PGSD Indonesia, 2025)
This study aims to systematically analyze the effect of self-efficacy on the independence and learning activity of elementary school students. The study uses a Systematic Literature Review (SLR) approach to synthesize the results of previous studies relevant to the topic of self-efficacy in basic education. The literature search was conducted through the Google Scholar database using appropriate keywords, then articles were selected based on inclusion and exclusion criteria, namely research articles on elementary school students, published within the last five years (2021–2025), and discussing the relationship between self-efficacy and independence or learning activity. A total of 15 selected articles were analyzed using qualitative descriptive analysis and synthesized based on the focus of the study. The results of the study indicate that self-efficacy has a positive and significant effect on the independence and learning activity of elementary school students. High self-efficacy is associated with perseverance in learning, self-directed learning abilities, learning motivation, learning engagement, and active student participation in learning. In addition, the learning context, the role of teachers, parental support, and extracurricular activities also strengthen the formation of students' self-efficacy. This study confirms that self-efficacy is an important psychological foundation in shaping independent and active learning behaviors in elementary school students, so it needs to be considered in the design of learning.